2018
DOI: 10.4103/ijabmr.ijabmr_423_17
|View full text |Cite
|
Sign up to set email alerts
|

Lack of awareness of pharmacovigilance among young health-care professionals in India: An issue requiring urgent intervention

Abstract: Background:Young healthcare professionals (HCPs) are the pillar of healthcare system. The objective of the present study was to assess the knowledge, attitude, and practices of young HCPs regarding adverse drug reactions (ADRs) reporting.Methods:This cross-sectional questionnaire-based study was conducted on young HCPs in a tertiary care teaching hospital of North India. The study instrument was semi-structured, prevalidated questionnaire. The responses obtained were compared among doctors and nursing professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…Apesar de ter obtido fraca correlação, o resultado de que quanto menor a idade do profissional, maior o escore de conhecimento em farmacovigilância, pode ser explicado devido ao fato de que o envelhecimento pode afetar as estratégias de desenvolvimento profissional, em decorrência, por exemplo, de menor propensão a participar de atividades contínuas de aprimoramento a partir dos 50 anos. Corroborando esse cenário, profissionais jovens constituem a base da força de trabalho dos sistemas de saúde e da implementação de novos programas de assistência médica, afastando os profissionais mais velhos de iniciativas de atualização e inovação (13)(14) .…”
Section: Discussionunclassified
“…Apesar de ter obtido fraca correlação, o resultado de que quanto menor a idade do profissional, maior o escore de conhecimento em farmacovigilância, pode ser explicado devido ao fato de que o envelhecimento pode afetar as estratégias de desenvolvimento profissional, em decorrência, por exemplo, de menor propensão a participar de atividades contínuas de aprimoramento a partir dos 50 anos. Corroborando esse cenário, profissionais jovens constituem a base da força de trabalho dos sistemas de saúde e da implementação de novos programas de assistência médica, afastando os profissionais mais velhos de iniciativas de atualização e inovação (13)(14) .…”
Section: Discussionunclassified
“…However, in a study performed in Bulgaria, this rate was lower (37.4%). Ergün et al reported that only 8% of the physicians did ADR reporting and Altıntaş Aykan et al showed that none of the physicians found to make any ADR reporting (15,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…However ignorance, lack of training and motivation in reporting of ADRs are the major obstacles in achieving the objectives of National PV programmes. 4 Lopez-Gonzalez et al, mentioned that "medical specialty was the most closely associated profession with under-reporting in 76% of studies". 3 It is evident from various studies that reporting of ADRs by healthcare professionals increased after training.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the most important taskforce group of medical students and catching them young so that they are knowledgeable and motivated enough to report any ADRs encountered in their future practice, would be a shot in the arm for the efforts of the Pharmacovigilance Programme of India (PvPI), initiated by the Central Drugs Standard Control Organization, New Delhi in 2010. 4 Although numerous studies have been conducted in the past to know the awareness levels amongst the medical fraternity, a very few have aimed to assess the outcome of interventional training programs on the knowledge and perception of pharmacovigilance in medical students. 5,6 Hence this study was aimed to assess the short and long-term impact of training programs on the awareness and knowledge of pharmacovigilance amongst II MBBS students.…”
mentioning
confidence: 99%